IL-17A inhibitions of indole alkaloids from traditional Chinese medicine Qing Dai. (12th June 2020) - Lee, Chia-Lin; Wang, Chien-Ming; Kuo, Yueh-Hsiung; Yen, Hung-Rong; Song, Ying-Chyi; Chou, Yu-Lun; Chen, Chao-Jung
Abstract: Ethnopharmacological relevance: Qing Dai, a famous traditional Chinese medicine (TCM), is prepared by a traditional fermentation process with the aerial part of Strobilanthes cusia . Currently, this TCM could treat various clinical inflammatory diseases, such as ulcerative colitis and psoriasis, however, the bioactive components of Qing Dai are unknown clearly. Aim of the study: To isolate and identify the anti-IL-17A components of Qing Dai. Materials and methods: Silica, RP-18 gels, and size exclusion resin were used for column chromatography to isolate the pure compounds. The structures of isolates were elucidated by NMR, MS, UV, IR spectra, and optical rotation. IL-17A protein and gene expressions were also evaluated in the Th17 cell model and luciferase reporter assay, respectively. Results: Two indole alkaloids, including one new indigodole D and cephalandole B, were isolated from Qing Dai. Indigodole D could inhibit IL-17A protein production during the Th17 polarization (EC50 : 2.16 μg/mL) or after the polarization (EC50 : 5.99 μg/mL) without cytotoxicity toward Th17 cells. Cephalandole B did not inhibit the IL-17A protein secretion. Nevertheless, both isolates notably inhibited IL-17A gene expression, especially cephalandole B, in a dose-dependent manner in Jukat cells with IL-17A luciferase reporter. Conclusions: Indole alkaloids, indigodoles A, C, D, tryptanthrin, and indirubin could contribute to anti-IL 17A properties of Qing Dai. The possible biogenetic mechanisms of above-mentioned indoles were also speculated in this investigation for further promising anti-IL-17 lead drugs development. Graphical abstract: Image 1